Shifting philanthropic engagement: moving from funding to deliberation in the eras of the COVID -19 global pandemic and black lives matter. Issue 2 (3rd July 2022) - Kraeger, Patsy
ABSTRACT: Institutional Philanthropy has the opportunity to rethink its role and build trust and deeply engage with communities beyond grantmaking in minority communities in the United States. The global pandemic highlights inequalities in the United States from health inequality to social inequalities. Institutional philanthropy can focus on doing more than giving money; organization leaders and program staff can deliberately engage and listen to communities and the public to drive systems change. This commentary examines the role of philanthropic foundations and philanthropic support organizations regarding advocacy, public policy and community listening when philanthropy has been asked to step up to deliver increased funding given the increases in COVID-19 cases and deaths in minority communities in light of the toll the pandemic has taken on minority communities, the unjust death of George Floyd and others and the Black Lives Matters movement. Philanthropic foundation leaders are faced with "the fierce urgency of now" to change organizational behavior from the relational to meaningful community engagement and social cohesion.